Autobiographical notes and other writings of historical interest - Ghose, Aurobindo, 1872-1950.; Sri Aurobindo Ashram (Pondicherry : Sri Aurobindo Ashram, 2006)
Chiefly letters of the Indian philosopher.
Keywords: Ghose, Aurobindo, -- 1872-1950 -- Correspondence; Ghose, Aurobindo, -- 1872-1950.; Philosophers -- India -- Correspondence